Adenocarcionma Of Mullerian Origin masquerading as an ovarian tumour- a rare case report. - Dr. Sujata Sarangi; Dr. Urvee Sarkar; Dr. Suchismita Chakrabarti (Tropical Journal of Pathology and Microbiology, 2017)
Objective: To create awareness about this rare tumour and the way it can mislead the clinician into believing it to be of an ovarian origin. Case report: A 50 years old postmenopausal female presented with a partly solid-partly cystic mass noted arising from the mesentery of sigmoid colon, obliterating the pouch of douglas and adhered to the posterior surface of uterus and right adnexa. The histopa thological features were suggestive of Adenocarcinoma of Mullerian origin. Conclusion: Great caution and precision are needed to ascertain the origin and management of these tumours as they carry a bad prognosis.